Sugarcane bagasse reinforced PVC: from waste to green composites - Wirawan, Riza; Salit, Mohd Sapuan; Yunus, Robiah; Abdan, Khalina (2009)
Sugar industry produces a large mass of sugarcane bagasse wastes. If not suitable treated, the wastes have an extremely harmful effect upon the environment. As a result, utilisation of sugarcane bagasse would be a positive contribution to environment and economic development. This paper presents the potential use of sugarcane bagasse to be utilised as reinforcing agent in PVC composites. It is found that the incorporation of sugarcane bagasse into PVC matrix may improve the strength and stiffness of the material.